A cross-sectional survey on the use of herbal tea among Cameroonian adults (18-65 years) - Abenwie Suh Nchang; Sylvia Njong; Sandra Fankem Noukimi; Lahngong Methodius Shinyuy; Sylvie Bambara; Edgar M. Kalimba; Joseph Kamga; Jacob Souopgui; Stephen Mbigha Ghogomu; Michel Frederich; Jean Lesort Louck Talom; Annie Robert (BMC, 2023)
Abstract Background In respect of the WHO's commendation to incorporate traditional medicine (TM) in health care, the Cameroon government wants to promote the use of the traditional medicine and is resolute on encouraging the treatment of patients with alternative medicine from traditional sources. This study explores the use of herbal tea by Cameroonian adults to prevent or treat diseases and the socio-demographic determinants of tea use among participants. Methods A cross-sectional survey was conducted among 307 Cameroonian adults (18-65 years) randomly selected within 4 hospitals and 4 communities in the Centre and Southwest regions of Cameroon between 04/01-20/04/2022, using interviewer administered semi-structured questionnaires. Binary logistic regression analysis was conducted to determine the association between variables. Results Over four-fifth (89.3%) of participants had taken herbal teas at least once within the last 2 years prior to the survey, and most participants used the teas for the prevention and treatment of Covid-19 (67.9%), malaria (59.7%) and typhoid fever (35%). Most respondents took the teas warm (75%), and the treatment dosage used by most respondents (51%) was "one glass in the morning and evening for one to two weeks". The teas taken by 70% of users had bad or bitter taste and 52.2% of them were uncomfortable with the bad taste. However, the majority of users completed their treatment dosage (72%), 90.5% of them were willing to use teas for treatment if prescribed in health facilities in future, and 90.1% were in support that herbal teas should be prescribed in hospitals. There was no significant association (p ≥ 0.05) between sociodemographic characteristics of participants and herbal tea use. However, the major motivating factor for acceptability of herbal tea use was treatment effectiveness (52.7%). Conclusion There is high prevalence of herbal tea use among adults Cameroonians in the studied settings in the Centre and Southwest regions of Cameroon, with a positive opinion and willingness to use teas if prescribed in health facilities. Authorities must ensure the effectiveness and safety of traditional medicine served in health facilities, to enhance compliance and adequate use.